Analisa Pola Hidup Bersih dan Sehat Dosen Pendidikan Jasmani Selama Pandemi Covid-19 - Saputro, Arnaz Anggoro; Nuryadi, Achmad (JOURNAL RESPECS (Research Physical Education and Sports), 2022)
The background of this research is the increasing number of patients infected with the COVID-19 virus in Indonesia and in the world. This is greatly influenced by the clean and healthy lifestyle of the community. If this clean and healthy lifestyle can be carried out properly, then a person can minimize the risk of the virus. The purpose of this study was to determine a clean and healthy lifestyle during the Covid-19 pandemic. Physical Education Lecturer at STKIP PGRI Jombang. This research is a descriptive qualitative research, the instruments in this research are interview guides and questionnaires. The results of this study are that the lecturers of Physical Education STKIP PGRI Jombang and Universitas PGRI Adi Buana Surabaya have implemented a clean and healthy lifestyle both before and during the COVID-19 pandemic, namely by continuing to exercise. The types of sports that are mostly done during the COVID-19 pandemic with the highest percentage are Gymnastics, Jogging and Cycling. Meanwhile, for physical activity at home with the highest percentage that is mostly done is cleaning the house and cooking. By implementing a clean and healthy lifestyle and regularly exercising an average of at least 30 minutes per day, the Physical Education lecturer at STKIP PGRI Jombang and Universitas PGRI Adi Buana Surabaya is confident that with a fit and healthy body due to exercise, you will avoid Covid 19.